Preparation of Cu(In, Ga)(S, Se)2 absorber via CuGa-NaF-KF target and the influence of Na/K ratio. (July 2023) - Lin, Yi-Cheng; Wang, Chong-Lun; Hung, Yu-Jen
Abstract: In the current study, a Na + and K + were incorporated directly in the CuInGa metal precursor layer via sputtering using a CuGa-NaF-KF target. The material properties and photovoltaic performance of the Cu(In, Ga)(S, Se)2 (CIGSSe) absorber layers were then assessed as a function of Na/K ratio and preparation method. In experiments, it was found that an Na/K ratio of 1.13 was optimal in terms of device efficiency. When using a sputtering target of CuGa-NaF-KF to add Na + and K + at the same time, it was found that the inclusion of Na + improved the crystal quality of the absorber layer and prevented the sinking of Ga and subsequent formation of CuGaSe2 grains at the bottom of the absorber layer. The addition of K + was shown to reduce the formation of defects (VCu ) in the absorber layer and improve energy gap matching at the p-n junction. An excessively high Na/K ratio is associated with the precipitation of fine grains of the alkali selenide on the surface of the absorber layer, leading to increased current leakage and decreased device performance. The CuGa-NaF-KF samples presented a downward bending of the valence band to repulse electron holes at GBs, thereby facilitating the transmission of minority carriers. The CuGa-NaF-KF samples also favored the growth of crystals in the (112) preferred orientation, which was also beneficial to device performance. Compared with the CuGa-NaF target and the conventional soda glass sputtering methods, the CuGa-NaF-KF target has the best device efficiency of 12.83%. Graphical abstract: Image 1 Highlights: Na and K were incorporated directly in the CIG metal precursor layer via sputtering using a CuGa-NaF-KF target. Na/K ratio of 1.13 was optimal in terms of device efficiency. Excessively high Na/K ratio will precipitate the alkali selenide on the surface of absorber. The CuGa-NaF-KF target has the best device efficiency of 13.95%.